Automated Room System for Disabled People - SHA'ABANI, MOHD NURUL AL-HAFIZ (Multidisciplinary Applied Research and Innovation, 2023)
Room automation for OKU people. controlling home applicants through smart phone. This project was created because it can be very helpful for OKU who cannot do their own work and such devices can be a great help for these people. The aim of the project is to develop an Automated Room for OKU to have a better and quality life. The Arduino programming language must be familiarized. The next step involves getting the system to work wirelessly utilizing the Wi-Fi and wireless control through connection of internet to control lamp and fan appliances. After the hardware setup is finalized, a simple graphical user interface is created using a blynk application. When the virtual button on blink is pressed every component will start operating. When the Lamp 1 virtual button is pressed it will turn on Lamp 1. When the Lamp 2 virtual button is pressed it will turn on Lamp 2. When the Fan virtual button is pressed it will turn on the fan. When the Buzzer virtual button is pressed it will turn on the buzzer. A room automation system can be very beneficial for someone who is half paralyzed. With the help of remote controls, they can control various aspects of their home such as lighting, fan, and emergency button without having to physically move around. This can greatly improve their quality of life and increase their independence.